Turismo e áreas protegidas : tendências globais e desafios para a integração de políticas públicas - Marta de Azevedo Irving; Marcelo Augusto Gurgel de Lima; Yasmin Xavier Guimarães Nasri (Confins)
Tourism represents a complex contemporary phenomenon that involves economic, social, environmental, ethical, political and symbolical dimensions and, for its interpretation, a multidimensional and interdisciplinary approach is essential, mediated by a critical political perspective. Nevertheless, tourism public policies are predominantly developed through a market or an economic bias, dissociated from other sectorial policies which tend to mask some essential issues in tourism planning. Based on these assumptions, this article aims to investigate, preliminarily, the global trends in terms of public policies aimed at the conservation of biodiversity, in its articulation with tourism, with emphasis on protected areas. The qualitative research was carried on based on bibliographic and documental analysis, considering the timeframe between 1992 - agreement by the Convention on Biological Diversity (CBD) - and 2019, year before the official Covid 19 Pandemic announcement. Evident efforts, at the global level, are recognized from the CBD, agreement, to articulate conservation of biodiversity and tourism public policies. However, this movement is still incipient in view of the growing risks to biodiversity and the urgency for tourism development on a sustainable basis, in the Post Covid 19 Pandemics context.